The use of ceftobiprole in treatment pathways in Spain: An expert panel review - Carmen Hidalgo-Tenorio; Francisco Javier Membrillo de Novales; Miguel Salavert Lleti; Laura Morata; Maria Rosa Oltra; Ángel Estella; David Nicolás; Maria Luisa Pedro-Botet; Andima Basterretxea Ozamiz; Jaime Lora-Tamayo (Journal of Global Antimicrobial Resistance, 2025)
Objectives: Ceftobiprole is a fifth-generation β-lactam approved in Spain solely for the treatment of community- and hospital-acquired pneumonia. The objectives of this study were to discuss the use of ceftobiprole in the Spanish healthcare setting, and to review and define its positioning for the treatment of infections, both in the hospital and outpatient settings. Methods: In November 2023, an in-person meeting was held, with 10 healthcare professionals with expertise in infectious diseases and/or hospital-at-home settings in attendance. Results: The experts discussed the use of ceftobiprole in treating community-acquired pneumonia (CAP) and hospital-acquired pneumonia (HAP), and in off-label indications where data exist to support this. In clinical trials and real-world studies, ceftobiprole has shown comparable efficacy and safety to other clinically approved antimicrobials for the treatment of skin and soft tissue, bone and joint, bacteraemia, and endocarditis infections. The panel considered the use of ceftobiprole in hospital and home/outpatient parenteral antimicrobial therapy settings for all indications discussed. Conclusions: Experts concluded that ceftobiprole may be a suitable alternative therapy in complex infections caused by Gram-positive and select Gram-negative bacteria. They agreed that the use in CAP and HAP could be expanded and that there was potential for use in all unlicensed indications discussed. The panel noted the benefits of its broad spectrum in polymicrobial infections, whereas the ability to administer the drug by continuous perfusion could enable its use in outpatient settings. Further research could highlight its suitability across additional conditions and populations.